Peningkatan Kebugaran Jasmani Melalui Gerakan Senam Ritmik Anak Indonesia Untuk Atlet Disabilitas National Paralympic Committee - Sari, Mawar; Sari, Suci Perwita; Asbi (CERED Indonesia Publishing, 2025)
This training program aimed to improve the physical fitness of disabled athletes under the National Paralympic Committee (NPC) of North Sumatra Province through the application of Indonesian rhythmic gymnastics for children. The training method was adaptive and inclusive, tailored to the type and degree of each athlete’s disability. Conducted over several weeks, the program focused on enhancing muscular strength, flexibility, motor coordination, and athlete confidence. The results showed significant improvements in physical fitness indicators, marked by increased stamina, body flexibility, and enthusiasm in training. The program also boosted the athletes’ motivation and readiness to compete in the 17th National Paralympic Week (PEPARNAS) in 2024, held in Solo, Central Java. This training has proven that a culturally rooted approach such as Indonesian rhythmic gymnastics can serve as an effective alternative in coaching programs for athletes with disabilities. It is expected that this model can be replicated in other regions as part of the broader development of disability sports in Indonesia